LOCAL WISDOM AS A FOUNDATION OF JUSTICE: EXAMINING POLYGAMY WITHIN ISLAMIC LAW IN SOUTH SULAWESI - Muhammadong, Muhammadong; Asroni, Ahmad; Achmad Widodo, Syukri Fathudin; Faizal, Nadya; Tahir, Tarmizi (Jurnal Al-Dustur, 2025)
In South Sulawesi, justice in polygamy is not merely a matter of law—it is a living dialogue between divine principles and ancestral wisdom. This study explores how local wisdom, particularly the adat system, serves as a foundational pillar of justice in the practice of polygamy under Islamic law. Employing a qualitative methodology, the research draws on interviews and document analysis involving religious leaders, community elders and affected families. The findings reveal that while Islamic law provides the formal legal framework, local customs deeply influence its interpretation and implementation. Adat norms ensure that polygamy is practiced with fairness, emphasizing the equitable treatment of wives, fulfillment of economic responsibilities and preservation of familial harmony. These traditions act as a moral compass, guiding the community to uphold justice in ways that resonate with their social values. Rather than conflicting with Islamic principles, local wisdom complements them—creating a hybrid system that is both legally sound and culturally sensitive. The study concludes that integrating local wisdom into formal legal structures can enhance the contextual relevance and social legitimacy of family law. It recommends a pluralistic approach to justice that honors both religious doctrine and indigenous knowledge, fostering a more humane and balanced legal practice.